Gender and non-medical use of prescription opioids: results from a national US survey. - Tetrault, Jeanette M; Desai, Rani A; Becker, William C; Fiellin, David A; Concato, John; Sullivan, Lynn E (Addiction (Abingdon, England), 2008)
Gender differences exist regarding alcohol and illicit drug use disorders in the United States. Little is known about the gender-related factors associated with non-medical use of prescription opioids.
Keywords: Adolescent; Adult; Aged; Analgesics, Opioid; Child; Data Collection; Drug Prescriptions; Female; Humans; Male; Mental Disorders; Middle Aged; Opioid-Related Disorders; Prevalence; Regression Analysis; Risk Factors; Sex Distribution; Sex Factors; Smoking; Street Drugs; United States